2018
DOI: 10.1002/app.46364
|View full text |Cite
|
Sign up to set email alerts
|

Calorimetric and rheokinetic analyses merged to capture crystallization kinetics in polyamide/clay nanocomposites: Revisiting predictability of models

Abstract: Crystallization kinetics of polymer/clay systems was the subject of numerous investigations, but still there are some ambiguities in understanding thermal behavior of such systems under isothermal and nonisothermal circumstances. In this work, isothermal rheokinetic and nonisothermal calorimetric analyses are combined to demonstrate crystallization kinetics of polyamide6/nanoclay (PA6/NC) nanocomposites. As the main outcome of this work, we detected different regimes of crystallization and compared them by bot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 56 publications
(118 reference statements)
1
2
0
Order By: Relevance
“…36 This was attributed to the addition of the submicron ABS phase restricting the growth of the PA6 crystals, which led to a reduction in crystallinity. Similar results were reported for montmorillonite/PA6, 17 clay/PA6, 37 and graphite fluoride platelets/PA6 38 composites. It was also found that the reactive blends had a higher crystallization rate than PA6 at the same cooling rate, meaning that the submicron ABS phase played a key role in heterogeneous nucleation.…”
Section: Resultssupporting
confidence: 89%
“…36 This was attributed to the addition of the submicron ABS phase restricting the growth of the PA6 crystals, which led to a reduction in crystallinity. Similar results were reported for montmorillonite/PA6, 17 clay/PA6, 37 and graphite fluoride platelets/PA6 38 composites. It was also found that the reactive blends had a higher crystallization rate than PA6 at the same cooling rate, meaning that the submicron ABS phase played a key role in heterogeneous nucleation.…”
Section: Resultssupporting
confidence: 89%
“…Network formation and network degradation are two possible cases, respectively, taking place by the release and receive of thermal energy. Designing advanced materials/ systems with specific functions requires application of well-documented criteria for optimization [33][34][35][36]. Addition of additives changes thermal characteristic of polymer systems, where mathematical modeling can bring about useful insights about events taking place in molecular level [37][38][39][40].…”
Section: Theory On Thermal Decomposition Analysismentioning
confidence: 99%
“…Recent investigations focused mainly on the properties and applications of PA6‐based nanocomposites containing various fillers, neat or modified, such as: multiwalled carbon nanotubes (MWCNs) able to generate a conductive network within the matrix, but with the formation of a transcrystalline layer on the nanotubes surface that can limit the transition insulating‐to‐conductive in the corresponding nanocomposites [ 12 ] ; sodium montmorillonite modified with a benzothiazolium salt, namely N‐dodecyl‐2‐methylbenzothiazolium iodide, that was able to impart enhanced thermal stability and improved mechanical characteristics to the composites upon reaching a good bulk dispersion [ 13 ] ; organically functionalized mica (methyl, tallow, bis‐2‐hydroxy‐ethyl, quaternary ammonium salt) modified the crystallization behavior of the corresponding PA6 nanocomposites under isothermal and non‐isothermal conditions [ 14 ] ; neat graphene oxide nanoparticles dispersed in PA6 using different solvent‐based protocols, followed by a melt mixing processing stage, allowed the formation of an interphase of notable strength [ 15 ] ; graphene oxide nanoparticles functionalized with poly(ε‐caprolactone) were employed in the in situ polymerization of PA6 when nanocomposites with enhanced interfacial adhesion yielded. [ 16 ]…”
Section: Introductionmentioning
confidence: 99%